2016
DOI: 10.1021/acsbiomaterials.6b00126
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Spectroscopic Screening of Osteosarcoma Living Cells on Stoichiometry-Modulated Silicon Nitride Bioceramic Surfaces

Abstract: Osteosarcoma cell viability, proliferation, and differentiation into osteoblasts on a silicon nitride bioceramic were examined as a function of chemical modifications of its as-fired surface. Biological and spectroscopic analyses showed that (i) postsintering annealing in N2 gas significantly improved apatite formation from human osteosarcoma (SaOS-2) cells; (ii) in situ Raman spectroscopic monitoring revealed new metabolic details of the SaOS-2 cells, including fine differences in intracellular RNA and membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 93 publications
2
37
0
Order By: Relevance
“…It showed a large number of areas with pronounced hydroxyapatite formation, which preferentially occurred at locations corresponding to the mixture of Si-Y-Al-O-N phases. While this observation confirmed previous findings89, it was newly revealed that there were surface depressions in the vicinity of the apatite deposits. We have interpreted this finding as evidence that the SaOS-2 cells actually scavenged molecules from the Si-Y-Al-O-N phases and apparently consumed them to produce bony apatite.…”
supporting
confidence: 92%
“…It showed a large number of areas with pronounced hydroxyapatite formation, which preferentially occurred at locations corresponding to the mixture of Si-Y-Al-O-N phases. While this observation confirmed previous findings89, it was newly revealed that there were surface depressions in the vicinity of the apatite deposits. We have interpreted this finding as evidence that the SaOS-2 cells actually scavenged molecules from the Si-Y-Al-O-N phases and apparently consumed them to produce bony apatite.…”
supporting
confidence: 92%
“…Regarding the mechanism of Saos‐2 cell adsorption, proliferation, and HAp mineralization, it has been previously shown that SiYAlON possesses a zwitterionic‐like surface at physiologic pH due to intermixing of surface moieties exhibiting negative (Si–O ‐ ) and positive (Y OH2+, Al OH2+, Si NH3+) charges . Surfaces engineered to exhibit zwitterionic character through grafting of polymers containing this functionality have also previously demonstrated extreme hydrophilicity due to their high degree of surface polarization .…”
Section: Discussionmentioning
confidence: 99%
“…These control discs consisted of both as‐fabricated (AFSN) and nitrogen‐annealed (N 2 ASN) Si 3 N 4 . They were selected because they had previously demonstrated enhanced osteoconductive behavior using living Saos‐2 osteosarcoma cells . When not being evaluated, all samples were stored in a desiccating cabinet to minimize inadvertent surface contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this twofold purpose in mind, a minor fraction of Si 3 N 4 particles was incorporated into a PEEK matrix. Si 3 N 4 was selected because the surface chemistry of this nonoxide bioceramic has previously demonstrated both bacterial lysis and enhanced bone formation . These properties resulted from its biologically friendly silicon/nitrogen surface chemistry and its slow elution rate which was suitable for implant applications.…”
Section: Introductionmentioning
confidence: 99%